2016
DOI: 10.4162/nrp.2016.10.2.175
|View full text |Cite|
|
Sign up to set email alerts
|

Onion peel extract reduces the percentage of body fat in overweight and obese subjects: a 12-week, randomized, double-blind, placebo-controlled study

Abstract: BACKGROUND/OBJECTIVESThe anti-obesity effect of quercetin-rich onion peel extract (OPE) was suggested in rats, but information from human studies is limited. This study aimed to investigate the effects of OPE on the body composition of overweight and obese subjects.MATERIALS/METHODSIn this 12-week, randomized, double-blind, placebo-controlled study, parallel clinical trials were performed in overweight and obese Korean subjects. Randomly assigned subjects were instructed to take daily either the placebo (male,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 28 publications
2
59
0
1
Order By: Relevance
“…Although many cell culture and animal studies focused on the beneficial effects of quercetin in obesity, there are only a limited number of human studies and clinical trials that have been performed to evaluate the effects of quercetin on obesity treatment. In a 12-week, randomized, double-blind, placebo-controlled study, Lee et al demonstrated that quercetin (100 mg/day/subject) significantly decreased the total body fat, particularly in the percentage of fat in the arm, and decreased the body mass index (BMI) of overweight or obese subjects [ 54 ]. Another study evaluated the effects of quercetin on obesity in overweight-obese subjects with various apolipoprotein E (APOE) genotypes; the authors reported that quercetin (150 mg/day/subject) decreased the waist circumference and triacylglycerol concentration [ 55 ].…”
Section: Quercetinmentioning
confidence: 99%
“…Although many cell culture and animal studies focused on the beneficial effects of quercetin in obesity, there are only a limited number of human studies and clinical trials that have been performed to evaluate the effects of quercetin on obesity treatment. In a 12-week, randomized, double-blind, placebo-controlled study, Lee et al demonstrated that quercetin (100 mg/day/subject) significantly decreased the total body fat, particularly in the percentage of fat in the arm, and decreased the body mass index (BMI) of overweight or obese subjects [ 54 ]. Another study evaluated the effects of quercetin on obesity in overweight-obese subjects with various apolipoprotein E (APOE) genotypes; the authors reported that quercetin (150 mg/day/subject) decreased the waist circumference and triacylglycerol concentration [ 55 ].…”
Section: Quercetinmentioning
confidence: 99%
“…Recently, Yang and Kim [19] demonstrated that the obesity index (% fat, BMI, waist circumstance) were significantly decreased by OPE intake for 12 weeks in obese university women. Previously, we reported that OPE supplementation significantly reduced the weight and percentage of body fat in overweight and obese adults [11]. We also reported that OPE supplementation significantly reduced waist and hip circumferences compared with baseline values while the changes observed in body weight and BMI were not statistically significant after 12 weeks of supplementation [12].…”
Section: Discussionmentioning
confidence: 89%
“…It has been known to have anti-diabetes, anti-obesity, and anti-hypertensive effects in animal and human studies [78910]. Recently, we reported that 12-week supplementary intake of quercetin-rich onion peel extract (OPE) significantly decreased body weight and percentage of body fat in overweight and obese adults [11]. We also have demonstrated that quercetin-rich OPE consumption for 12 weeks may exert antioxidative activity by preventing the reduction of superoxide dismutase (SOD) activity as well as the production of reactive oxygen species (ROS) in obese women [12].…”
Section: Introductionmentioning
confidence: 99%
“…All openings including donor top and receptor arm were occluded with parafilm ® to prevent solvent evaporation. At regular time intervals (5,10,15,30,45, 60, 120, 240, 300, 360, 420, 480, 1440 and 2880 min) samples of the receiving phase were withdrawn and OLE content was measured by a UV-vis spectrophotometer (UV-Visible Agilent model 8453, Agilent Technologies, Cernusco sul Naviglio MI, Italy) accomplished using a standard curve in SWF (λ max = 280.0 nm, r = 0.9998). All experiments were performed in triplicate, each result represents an average of three measurements and the error was expressed as standard deviation (±SD).…”
Section: In Vitro Release Of Extract From the Hydrogel Filmmentioning
confidence: 99%
“…The common onion (Allium cepa L.) is a worldwide cultivated vegetable used both as food and also in the health field for the presence of bioactive molecules mainly endowed with antioxidant activity [1][2][3]. Many scientific studies on the lipid-and glucose-lowering [4][5][6][7][8], anti-inflammatory [9][10][11], antioxidant [12][13][14][15][16] and antibacterial [13] properties of onion extracts have been published. Our previous work in this area reported the pungency determination [17] and the antioxidant and immune modulatory activities of purple-skin Rojo Duro onion extracts [18].…”
Section: Introductionmentioning
confidence: 99%